Monoamine Oxidase Inhibitors: A Review of Their Anti-Inflammatory Therapeutic Potential and Mechanisms of Action - Mahyar Ostadkarampour; Edward E. Putnins (Frontiers Media S.A., 2021)
Chronic inflammatory diseases are debilitating, affect patients' quality of life, and are a significant financial burden on health care. Inflammation is regulated by pro-inflammatory cytokines and chemokines that are expressed by immune and non-immune cells, and their expression is highly controlled, both spatially and temporally. Their dysregulation is a hallmark of chronic inflammatory and autoimmune diseases. Significant evidence supports that monoamine oxidase (MAO) inhibitor drugs have anti-inflammatory effects. MAO inhibitors are principally prescribed for the management of a variety of central nervous system (CNS)-associated diseases such as depression, Alzheimer's, and Parkinson's; however, they also have anti-inflammatory effects in the CNS and a variety of non-CNS tissues. To bolster support for their development as anti-inflammatories, it is critical to elucidate their mechanism(s) of action. MAO inhibitors decrease the generation of end products such as hydrogen peroxide, aldehyde, and ammonium. They also inhibit biogenic amine degradation, and this increases cellular and pericellular catecholamines in a variety of immune and some non-immune cells. This decrease in end product metabolites and increase in catecholamines can play a significant role in the anti-inflammatory effects of MAO inhibitors. This review examines MAO inhibitor effects on inflammation in a variety of in vitro and in vivo CNS and non-CNS disease models, as well as their anti-inflammatory mechanism(s) of action.